COLQ variant associated with Devon Rex and Sphynx feline hereditary myopathy. (16th September 2015) - Gandolfi, Barbara; Grahn, Robert A.; Creighton, Erica K.; Williams, D. Colette; Dickinson, Peter J.; Sturges, Beverly K.; Guo, Ling T.; Shelton, G. Diane; Leegwater, Peter A. J.; Longeri, Maria; Malik, Richard; Lyons, Leslie A.
Summary: Some Devon Rex and Sphynx cats have a variably progressive myopathy characterized by appendicular and axial muscle weakness, megaesophagus, pharyngeal weakness and fatigability with exercise. Muscle biopsies from affected cats demonstrated variable pathological changes ranging from dystrophic features to minimal abnormalities. Affected cats have exacerbation of weakness following anticholinesterase dosing, a clue that there is an underlying congenital myasthenic syndrome (CMS). A genome‐wide association study and whole‐genome sequencing suggested a causal variant for this entity was a c.1190G>A variant causing a cysteine to tyrosine substitution (p.Cys397Tyr) within the C‐terminal domain of collagen‐like tail subunit (single strand of homotrimer) of asymmetric acetylcholinesterase ( COLQ ). Alpha‐dystroglycan expression, which is associated with COLQ anchorage at the motor end‐plate, has been shown to be deficient in affected cats. Eighteen affected cats were identified by genotyping, including cats from the original clinical descriptions in 1993 and subsequent publications. Eight Devon Rex and one Sphynx not associated with the study were identified as carriers, suggesting an allele frequency of ~2.0% in Devon Rex. Over 350 tested cats from other breeds did not have the variant. Characteristic clinical features and variant presence in all affected cats suggest a model for COLQ CMS. The association between the COLQ variant and this CMS affords clinicians the opportunity to confirm diagnosis via genetic testing and permits owners and breeders to identify carriers in the population. Moreover, accurate diagnosis increases available therapeutic options for affected cats based on an understanding of the pathophysiology and experience from human CMS associated with COLQ variants.